Current Pharmaceutical Approach to Investigate the Impact of Polycyclic Aromatic Hydrocarbons in Cigarette Smoke on Human Health (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study investigates the impact of polycyclic aromatic hydrocarbons (PAHs) in cigarette smoke on human health using laboratory, pharmacokinetic, and epidemiological approaches. The cohort included smokers (≥1 cigarette/day for the past year) and non-smokers, aged 18-65. Biological samples (blood, urine, buccal cells) were analyzed to quantify oxidative stress biomarkers and PAH exposure, utilizing gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC). Participants were evaluated annually, and data was analyzed using multivariate regression and Kaplan-Meier survival analysis over five years. Results showed a balanced age distribution (25% aged 36-45) and a predominance of males (65%). Socioeconomic analysis indicated 60% from high, 40% from middle, and 20% from low backgrounds. Smokers exhibited significantly elevated levels of PAH metabolites, inflammatory markers, oxidative stress biomarkers, and DNA damage compared to non-smokers. HPLC and GC-MS analyses revealed higher PAH metabolite concentrations in blood samples than in urine. This study underscores the significant health risks associated with PAH exposure from cigarette smoke, highlighting elevated PAH metabolites, DNA adducts, and inflammatory markers among smokers and emphasizing the need for enhanced detection and prevention strategies.